Utilising ubuntu in social work practice: ubuntu in the eyes of the multimodal approach - Chigangaidze, Robert K. (Routledge, 2022)
African social workers and psychologists have called for the utility of ubuntu philosophy in the fields of social work and psychology. Ubuntu is an African philosophy that is based on humanness, kindness, communality, socio-structural issues such as social justice, and human rights. This paper explores the philosophy of ubuntu guided by the seven modalities of the multimodal approach, which are behaviour, effect, sensation, imagery, cognition, interpersonal relationships and drugs/biology. The article suggests that ubuntu as an African philosophy has potential to contribute two modalities in addition to the seven modalities in the multimodal approach by the South African psychologist Arnold Lazarus. It argues that ubuntu contributes two domains in assessments and these are as follows: the person-physical environment relationship and the spiritual relationship. Given the emphasis on eco-spiritually informed social work, this paper calls for the adoption of these two modalities for the assessment and intervention plans in social work practice.